Pengaruh Penambahan Latihan Isometrik Pada Intervensi Ultrasound Terhadap Peningkatan Aktifitas Fungsional Pada Pasien Osteoarthritis Lutut - Fatoni, Zulfi Rohmat, Totok Budi Santoso , S.Fis , MPH (2016)
Osteoarthritis is a clinical syndrome due to changes in the structure of cartilage and surrounding tissues that is characterized by progressive depletion of cartilage accompanied by new bone formation on trabecular subchondral and formation of new bone at the edges of the joint. Isometric strengthening exercises are static form of exercise where muscles contract and generate force without any change in muscle length and without movement joints. This research aims to determine the effect of isometric exercise in intervention ultrasound to increased functional activity for the patient osteoarthritis of knee. This research uses experimental. Pre and post test group design with 2 the treatment group is given intervention ultrasound and the control group is given the addittion isometric exercise by intervention ultrasound. The result shown that one group gets P value = 0,018 (p < 0,005) while two group gets P value = 0,011 (p < 0,005) and the influence of different test after the treatment between the two group get P value = 0,002 (p < 0,005). Intervention ultrasound and isometric exercise in patients with osteoarthritis knee of knee have influence to the functional activity, however there are significant differents.